Variation in Symmetry Around Doped Pr(III) Ion in Saturated Solution of Medicinal Compounds with Reference to Judd-Ofelt Electronic Spectral Parameter - Aryamitra Pandey, Ms.; soni, k.P.; Joshi, G.K. (Asian Journal of Chemistry, 2010)
The interaction of medicinal compounds with Pr(III) ion in the form of doped model have been discussed in terms of covalency (β) and Judd-Ofelt symmetry (T4/T6) parameters as derived from f↔f transitions. The doped model involves small concentration of Pr(III) ion salt in saturated solution of medicinal compounds in alcohol. The medicinal compounds include anthelminthic drugs, viz., thiabendazole, piperazine, mebendazole, pyrantel pamoate, albendazole, levamisole, diethylcarbamazine, antimicrobial drugs, viz., sulfaacetamide, sulfadiazine, sulfaguanidine, sulfamethoxazole, pefJoxacin, ciprofioxacin, tinidazole, metronidazole, atovaquone, pentamidine and anti anginal drugs, viz., amIodipine, atenolol and nifedipine. It also describes electronic spectral characterization in terms of various parameters. The linear relationship between oscillator strength (P) and VT4/vT6 has been discussed with reference to hypersensitive transition, i.e., 3P2 band of Pr(III) ion.